The Development Strategy of Porang Commodities (Amorphophallus oncophyllus) in Moramo Sub District South Konawe Regency using AHP Method - Megawati Megawati; Rosmawaty Rosmawaty; Muhammad Aswar Limi (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2022)
This study aims to find out what criteria affect the development of Porang crop commodities in Moramo Sub District, South Konawe Regency, what alternative strategies can be applied in the development of Porang crop commodities in Moramo Sub District, South Konawe Regency, what strategy priorities can be implemented in the development of Porang plant commodities in Moramo Sub District, South Konawe Regency. The determination of location is determined deliberately. Data collection will be carried out from September 2021 to April 2022. The sampling technique in this study was determined by the Purposive Sampling technique, where sampling resolved specific characteristics that followed the research objectives. The samples in this study were farmers, traders, and government agencies. Data analysis in this study used the AHP method. The results showed that the priority strategies that can be applied to the development of porang crop commodities in Moramo Sub District, South Konawe Regency, namely utilizing government support with a weight value of (0.374), holding counseling activities with a weight value of (0.324), developing resources with a weight value of (0.302).